Influencia de la educación ambiental en la formacion de conciencia ambiental en los educandos a nivel basica y de bachillerato en el canton Buena Fe, provincia de Los Rios, durante el periodo 2013 - Egúez Alvicar, Andrea Elizabeth (2014)
Environmental education today has become one of the most mentioned global issues of great importance today, why , the academic curriculum of the educational units have endeavored to include such learning and knowledge on all environmental problems experienced today. Although there are several tools to achieve human awareness to the environment in order to achieve or exceed environmental values. In this project the student’s initial knowledge obtained through their teachers or experiences about the care of the environment and the use of waste generated in various activities is valued. Then knowledge in each of the institutions were given to expand its capabilities , and encourage creativity , participation and group work , as elements of an active methodology , reinforced with practical workshops, where all recyclable materials are reused . Then the level of knowledge acquired by the students is evaluated to determine its acceptance and finally with data from the training plan was built and other activities to improve the environmental awareness of each school selected student and generate actions of the importance to put into practice responsible use, showing the different crafts made from recycled materials, thus creating, expectation and even proposing it as a source of income on a larger scale. The research was conducted through review and analysis of documents, articles, texts and others, all related to environmental education. It invites educational institutions put much into practice certain procedures with environmental solid waste, to help them reduce or control pollution and improve its image, which in turn led to better conservation and environmental awareness.